2018
DOI: 10.1186/s40634-018-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of residency training on arthroscopic knot tying and knot stability: which knot is best tied by Orthopaedic surgery residents?

Abstract: BackgroundThe aim of this study is to evaluate which of three arthroscopic knots are most reliably taught to and executed by residents at varying levels of training.MethodsThree arthroscopic knots, the Samsung Medical Center (SMC), the Weston, and the surgeon’s knot, were taught to 16 orthopaedic surgery residents. Each knot was tied in triplicate at two sessions 1 week apart. The knots were then biomechanically tested for strength. Corresponding knots tied by a sports medicine fellow served as the respective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…18 However, in practice, the arthroscopic knot utilized is often determined by surgeon preference, training, and experience. 7,11,14 In a study by Baumgarten and Wright, 4 an internet-based survey was used to determine arthroscopic knot preferences of American Orthopaedic Society for Sports Medicine members. Interestingly, the survey 4 demonstrated that most surgeons rely on experience and preference of a knot type over biomechanical evidence, with only 17.4% of respondents basing their knot tying on a literature review and the majority using the same knot configuration for all arthroscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, in practice, the arthroscopic knot utilized is often determined by surgeon preference, training, and experience. 7,11,14 In a study by Baumgarten and Wright, 4 an internet-based survey was used to determine arthroscopic knot preferences of American Orthopaedic Society for Sports Medicine members. Interestingly, the survey 4 demonstrated that most surgeons rely on experience and preference of a knot type over biomechanical evidence, with only 17.4% of respondents basing their knot tying on a literature review and the majority using the same knot configuration for all arthroscopic procedures.…”
Section: Discussionmentioning
confidence: 99%